The effectiveness of the perceived sensory in the formation of the semantic dimension of cinematic picture in the "Well" film. - Benrabia, Mohamed Amine; Mansouri, Mohamed (Journal of Human Sciences, 2020)
Perceptive is an instrument of knowledge and a component of human consciousness, and cinema in its power and luster, which refers more to sensory perception, because it based on aesthetic taste, surprising optics, provoking feelings and imagination, and stimulating rational perception. So the film’s delivery tool cannot be abstract; there is no film without pictures, cinematic imagination, visual creativity, sound effects, makeup, lighting and colors, all of which contribute to creating narration with illusion, and bringing the viewer to the heights of enjoying what he sees, as the message that worked Film makers to notify it. The well movie directed by Lotfi Bouchouchi has all the sensory perceptions that will form the cinematic picture that the viewer aspires to see in the movie.